2014
DOI: 10.1590/s2317-64312014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre distúrbio de voz e sintomas de disfunção temporomandibular autorreferidos por professores

Abstract: Objetivo : Verificar a relação entre distúrbio de voz e sintomas de disfunção temporomandibular em professores do ensino fundamental. Métodos : Participaram deste estudo 138 professores, 96 do gênero feminino e 42 do gênero masculino, com média de idade de 38 anos. Os professores responderam questionário, com cinco questões de autorreferência à presença de alteração de voz no presente e sintomas de disfunção temporomandibular. Os dados foram analisados por meio de teste de associação (Qui-quadrado) para veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
4
0
7
Order By: Relevance
“…Recent studies evaluating TMD in teachers showed a higher prevalence in females. But in this study the same assertion cannot be made, since the sample composed of 49 teachers presents a higher proportion of females than males, however, all the teachers who participated in our research presented some degree of TMD (7,18) . In some studies, the simplified anamnestic questionnaire, Fonseca's Anamnestic Index was used, which was elaborated according to the Helkimo anamnestic Index.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Recent studies evaluating TMD in teachers showed a higher prevalence in females. But in this study the same assertion cannot be made, since the sample composed of 49 teachers presents a higher proportion of females than males, however, all the teachers who participated in our research presented some degree of TMD (7,18) . In some studies, the simplified anamnestic questionnaire, Fonseca's Anamnestic Index was used, which was elaborated according to the Helkimo anamnestic Index.…”
Section: Discussionmentioning
confidence: 61%
“…Speech due to this disharmony is compromised. Prolonged use of the voice is a prerequisite for the appearance of severe laryngeal tension, pain symptoms in TMJ and difficulty in performing mandibular movements (7) . The execution of speech involves mobile and fixed organizers of the SS, which are controlled by the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El 36.4 % de los trabajos analizó las repercusiones vocales que provoca el aumento de la apertura mandibular (Austin, 2007;Mautner, 2015;Nair et al, 2016;Mercer & Lowell, 2019). El 18.1 % restante estudió los efectos que produce la función vocal sobre la mecánica de la ATM (Machado et al, 2014;van Selms, Wiegers, Lobbezoo, & Visscher, 2019) (tabla 2).…”
Section: Resultsunclassified
“…Studies about spoken voice show that the prevalence of some degree of dysphonia, assessed or self-reported in individuals who use their voice at work can reach 35,5% 29 , 43,3% 31 , 48% 7 , 50% 22,32 , 70% 33,34 , 80,7% 35 , 85% 26 e até 97,2% 36 , among others, a percentage higher than the 20% mentioned by colleagues.…”
mentioning
confidence: 83%